2007
DOI: 10.1038/sj.ejcn.1602948
|View full text |Cite
|
Sign up to set email alerts
|

How important is malnutrition? A prospective study in internal medicine

Abstract: We found a low prevalence (10%) of malnourished patients on admission. Clinical judgment and to some extent anthropometrical measurement were helpful for assessing the nutritional status, laboratory values were not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
(31 reference statements)
5
15
0
3
Order By: Relevance
“…Muitas questões necessitam treinamento do aplicador (como antropometria) ou implicam em julgamentos subjetivos. A MNA -SF almeja preservar a sensibilidade, a especificidade e o diagnóstico confiável da MNA original, enquanto minimiza tempo e treinamento necessários para a aplicação 3,21 .…”
Section: é T O D O Sunclassified
“…Muitas questões necessitam treinamento do aplicador (como antropometria) ou implicam em julgamentos subjetivos. A MNA -SF almeja preservar a sensibilidade, a especificidade e o diagnóstico confiável da MNA original, enquanto minimiza tempo e treinamento necessários para a aplicação 3,21 .…”
Section: é T O D O Sunclassified
“…A number of studies showed similar results. 8,9,11,[25][26][27] On the contrary, some studies indicated no significant relationship between the length of stay and the nutritional status. [28][29][30] When we analyzed the food choices of patients in this study, we found that malnourished and at risk patients consumed significantly less amounts of meat, poultry, fish, eggs, lentils, fruits and vegetables compared to the patients with normal nutritional status.…”
Section: Discussionmentioning
confidence: 93%
“…8,9,11,[18][19][20][21] Only a few studies assessed nutritional status of elderly hospitalized patients in Turkey. Korfalı and colleagues 22 found malnutrition risk as 25% using Nutritional Risk Screening 2002 (NRS-2002) in their study which included 62 hospitals and 10,325 patients 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug utilization analysis offered us further insights into the significant dynamics of NRS-2002 outputs to creatinine, which in our study was not related to weight loss due to eventual overuse of diuretics. There were no significant differences or correlations of percentage WLH with studied biochemistry diagnostics [28]. …”
Section: Discussionmentioning
confidence: 99%